The Carboxy-Terminal Segment of the Human Cytomegalovirus DNA Polymerase Accessory Subunit UL44 Is Crucial for Viral Replication - Silva, Laurie A. (American Society for Microbiology (ASM), 2010)
The amino-terminal 290 residues of UL44, the presumed processivity factor of human cytomegalovirus DNA polymerase, possess all of the established biochemical activities of the full-length protein, while the carboxy-terminal 143 residues contain a nuclear localization signal (NLS). We found that although the amino-terminal domain was sufficient for origin-dependent synthesis in a transient-transfection assay, the carboxy-terminal segment was crucial for virus replication and for the formation of DNA replication compartments in infected cells, even when this segment was replaced with a simian virus 40 NLS that ensured nuclear localization. Our results suggest a role for this segment in viral DNA synthesis.